1991
DOI: 10.1152/jappl.1991.70.2.554
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of rat limb bones to strenuous exercise

Abstract: We examined the influence of a strenuous exercise regimen on tibial and metatarsal bones to show not only how the geometric, histological, and mechanical properties of immature bone respond to strenuous exercise but also how long bones within the same limb may respond differentially to exercise. Female Sprague-Dawley rats (8 wk old) were divided randomly into two groups: a sedentary control (n = 15) and an exercised group (n = 15). The exercise intensity was 80-90% of maximum oxygen capacity 5 days/wk for 10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
1
21
0
3
Order By: Relevance
“…Structurally, the tissues are easily visibly distinguished from one another by the presence and absence of osteocytes, but are more similar to each other in gross, histological morphology than they are to the more-studied cellular bone types of amniotes. In particular, differences in osteocyte presence and associated canalicular density are striking, even for the cellular boned carp where osteocytes are much less densely packed than those of birds and mammals (424 vs 700-1800cellsmm -2 ) (Li et al, 1991;Skedros, 2005). The low osteocyte density, coupled with the apparent relative scarcity of blood vessels in both tilapia and carp bone, make both fish bone types observed here appear, at lower magnifications, as more solid (less porous) blocks of tissue compared with amniote bone, also suggesting they may have a lower metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally, the tissues are easily visibly distinguished from one another by the presence and absence of osteocytes, but are more similar to each other in gross, histological morphology than they are to the more-studied cellular bone types of amniotes. In particular, differences in osteocyte presence and associated canalicular density are striking, even for the cellular boned carp where osteocytes are much less densely packed than those of birds and mammals (424 vs 700-1800cellsmm -2 ) (Li et al, 1991;Skedros, 2005). The low osteocyte density, coupled with the apparent relative scarcity of blood vessels in both tilapia and carp bone, make both fish bone types observed here appear, at lower magnifications, as more solid (less porous) blocks of tissue compared with amniote bone, also suggesting they may have a lower metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…elliptical in shape with major and minor diameters of 10 and 5m, respectively (McCreadie et al, 2004;Hannah et al, 2010)] the area fraction taken by the osteocytic lacunae in carp bones is 1.6%. The osteocytic lacunae (black arrows in Fig.3C,E) in the bones of the carp show distinct canalicular networks interconnecting adjacent lacunae (black arrowhead in Fig.3E); however, their distribution is less dense than in mammals (R.S., personal observation) (Skedros, 2005;Li et al, 1991).…”
Section: Osteocyte Distribution and Densitymentioning
confidence: 99%
“…The early ontogeny aspect of the study is important to highlight because of varied outcomes in the literature. Results range from reduced limb length with exercise (Kiiskinen, 1977;Li et al, 1991;Bourrin et al, 1994;Reich et al, 2005), to no effect (Nyska et al, 1995;Niehoff et al, 2004;Fritton et al, 2005;Hamrick et al, 2006), to increased limb length with exercise (Beyer, 1896;Adams, 1938;Buskirk et al, 1956;Tomljenovic Borer and Kuhns, 1977;Swissa-Sivan et al, 1989;Losos et al, 2001;Iwamoto et al, 2004;Plochocki et al, 2008;Serrat et al, 2010). Although nutrition, trauma, pathology, sex, severity, and duration of exercise are all potential factors that might explain some of the discrepancies among these studies (particularly the reduced limb growth) (Rogol et al, 2000;Forwood, 2008), much of the remaining variation could be explained by simply examining the age of the subjects.…”
Section: Examples Of a Critical Age Period In Exercise Studiesmentioning
confidence: 99%
“…The results of animal research has shown that geometric, composition and growth properties may vary in different bones presumably as a function of the different loading histories at a particular site. Li et al (1991) examined the effect of strenuous exercise on the immature bone of rats. They found that the cross-sectional area of two sites differed, with an increase at the second metatarsus and a decrease in the tibia.…”
Section: Discussionmentioning
confidence: 99%